PENGARUH KUALITAS PELAYANAN DRIVER OJEK ONLINE TERHADAP KEPUASAN KONSUMEN PADA GOJEK AREA TANGERANG SELATAN - S, Mathodah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The level of competition between online motorcycle taxis cannot be avoided. Therefore, building relationships with consumers through providing satisfaction with service is absolute. The purpose of this study was to determine the effect of service quality on Gojek customer satisfaction in the South Tangerang. The research method used is quantitative with descriptive explanations. The sample technique used is Accidental Sampling with 96 respondents. The analytical method used is validity test, reliability test, correlation coefficient test, simple linear regression test, determination coefficient test and research hypothesis test. The results show that service quality has a significant effect on customer satisfaction. In other words, to be able to win the competition, one of thing should to do is making satisfaction on consumers. Therefore, Gojek needs to take concrete action in developing the driver's personality, namely friendly and helpful drivers. Through providing training and financial support (incentives) can be a good stimulus for drivers